2001
DOI: 10.1159/000054900
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in Patients Suffering from Post-Traumatic Stress Disorder

Abstract: Objective: The aim of the study was to determine whether regional cerebral blood flow in survivors of torture suffering from post-traumatic stress disorder (PTSD) differed significantly from that in healthy controls. Method: We examined the cerebral regional distribution of 99m-technetium-hexamethylpropyleneamineoxime (HMPAO) using single photon emission computed tomography (SPECT) in 8 patients and in 8 healthy controls. A semi-quantitative analysis was performed in which symmetrical regions of interest (ROI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…Furthermore, no changes were reported in the cerebellum, medial frontal cortex, and thalamus. Mirzaei et al [2001], using the same radiotracer, found an increase in left hemisphere rCBF in patients with PTSD who survived torture episodes. The most recent results, reported by Bonne et al [2003b], using 99m-Tc HMPAO, found decreased activity in the right precentral, superior temporal, and fusiform gyri, accompanied by increased rCBF in the cerebellum.…”
Section: Resting Paradigmsmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, no changes were reported in the cerebellum, medial frontal cortex, and thalamus. Mirzaei et al [2001], using the same radiotracer, found an increase in left hemisphere rCBF in patients with PTSD who survived torture episodes. The most recent results, reported by Bonne et al [2003b], using 99m-Tc HMPAO, found decreased activity in the right precentral, superior temporal, and fusiform gyri, accompanied by increased rCBF in the cerebellum.…”
Section: Resting Paradigmsmentioning
confidence: 82%
“…The most straightforward way of measuring brain activity is by observing a subject at rest. In PTSD, researchers have used both PET and SPECT to measure rCBF [Bonne et al, 2003b;Mirzaei et al, 2001;Seedat et al, 2004], glucose metabolism [Bremner et al, 1997], and the binding potentials for both benzodiazepine [Bremner et al, 2000;Fujita et al, 2004] and serotonin 1A [Bonne et al, 2005] receptors. Cerebral blood flow, and both receptor availability and affinity are all indirect measures of activity, or potential activity, in the brain.…”
Section: Functional Neuroimaging Paradigmsmentioning
confidence: 99%
“…Only few resting-state imaging studies of PTSD have been performed [62], [63], [64], [65], [66]. The findings are heterogenous and are not restricted to the default mode activity, even though abnormal resting-state activity in some areas of the DMN was observed in PTSD patients compared to healthy controls [62], [66].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, PTSD patients showed higher cerebral blood flow in the left hemisphere than in the right, most notably in the temporoparietal region [46] and in the projection area of the ventral basal ganglia [47]. …”
Section: Spect Studies Of Regional Cerebral Blood Flowmentioning
confidence: 99%